Efektivitas Pendidikan Kesehatan Video Animasi Tentang Pernikahan Dini Terhadap Pengetahuan Remaja Putri - Hanifa Andisetyana Putri; Shusmitha Sekar Satriani; Runjati (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2023)
Background: The phenomenon of early marriage during the COVID-19 pandemic thatoccurred in Batang Regency increased by 200% compared to the previous year withthe average age of marriage being 17 years. From 2019 to 2020 there has been adecrease of 0.6%, but it has not yet reached the target of reducing it to 8.74% in 2024.One of the factors causing early marriage is the lack of knowledge of reproductive health in adolescents and the risks that can occur due to contraceptives. reproductiveorgans that are not ready for pregnancy and childbirth. This can increase maternaland infant mortality as a standard for a country's health status. Social and economicimpacts also occur due to reduced peer interaction, discontinued education levels,resulting in narrower job opportunities.Purpose: The aim of this study was to determine the effectiveness of health educationthrough animated video media on young women's knowledge of early marriage duringa pandemic at SMA Negeri 1 Batang. This type of research uses a quasi-experimentaland pretest-posttest with control design. The sampling technique was simple randomsampling with a total of 134 respondents. Data collection used a questionnaire filledout online via the Google form.Result: The results of the study showed an increase in the average knowledge scorein both the control and experimental groups. In the control group, the increase in scorereached 12.69 ± 2.211, while in the treatment group it experienced a higher increase,namely 22.55 ± 7.509. The results of the Mann Whitney test showed that providinghealth education using animated video media was effective in increasing theknowledge of SMA Negeri 1 Batang students with a p value = 0.000.Keywords: early marriage, animation videos, knowledge